2015
DOI: 10.1016/j.schres.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

White matter development in the early stages of psychosis

Abstract: Schizophrenia has been conceptualized as a disorder of both neurodevelopment and a disorder of connectivity. One important aspect of the neurodevelopmental hypothesis is that schizophrenia is no longer thought to have discrete illness time points, but rather a long trajectory of brain changes, spanning many years, across a series of stages of the disease including the prodrome, first episode, and chronic period. As the disease progresses, there is a complex relationship between age related changes and disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 111 publications
5
54
0
Order By: Relevance
“…46 As we did not observe associations between DUI, negative symptoms and FA reductions (Table 3), our findings support the idea that only subtle white matter deficits in these regions are present at illness onset, but that these deficits disseminate and progress over time. 47 Our observation of FA reductions in the right CT is in line with findings in patients with early-onset schizophrenia and in individuals at high risk for psychosis. 48 However, deficits in this region are less frequently observed in later stages of illness, suggesting that FA changes in the CT may be more prominent at the time of illness onset.…”
Section: Discussionsupporting
confidence: 90%
“…46 As we did not observe associations between DUI, negative symptoms and FA reductions (Table 3), our findings support the idea that only subtle white matter deficits in these regions are present at illness onset, but that these deficits disseminate and progress over time. 47 Our observation of FA reductions in the right CT is in line with findings in patients with early-onset schizophrenia and in individuals at high risk for psychosis. 48 However, deficits in this region are less frequently observed in later stages of illness, suggesting that FA changes in the CT may be more prominent at the time of illness onset.…”
Section: Discussionsupporting
confidence: 90%
“…It is also worth noting that the SLF is a late-maturating tract, thus potentially more vulnerable to later neurodevelopmental disturbances during adolescence to early adulthood 50 or neurotoxic effects that take place around the onset of the first psychotic symptoms. 51 It was also noteworthy that patients with widespread and more prominent white matter abnormalities exhibited greater severity in negative symptoms than those with regional deficits. In fact, negative symptoms (ie, anhedonia, amotivation, and social dysfunction) were found to be related to specific white matter deficits in previous studies, notably with alterations in the corpus callosum, 52 uncinate, 53 SLF, 54 and ILF.…”
Section: 48mentioning
confidence: 99%
“…In addition, the secondary measures of radial (RD) and axial diffusivity (AD) are believed to more specifically index myelination and axonal organization, respectively (1618). The majority of DTI studies in schizophrenia have shown decreased FA in long-range association tracts, including the superior longitudinal fasciculus (SLF), cingulum bundle, uncinate fasciculus (UF), inferior longitudinal fasciculus (ILF) and arcuate fasciculus (1921). These long connection fibers likely facilitate inter-regional communication and support a wide range of cognitive abilities.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…For instance, a subset of studies has shown no patient-control differences (20, 2325), while others have found more global rather than regional effects (2628). It is an open question whether this is a function of disease state (21), of developmental stage (29), or of another factor, such as medication. It is also possible that differences in scan acquisition, motion correction, and analysis may contribute.…”
Section: Summary Of Findingsmentioning
confidence: 99%